Impact of use of neonicotinoid insecticides on honey bees in the cultivation on spring oilseed crops in Finland. Interim report - Ketola, Jarmo; Hakala, Kati (MTT, 2014)
The Neomehi project is studying how neonicotinoid-based plant protection products used in the cultivation of oilseed rape and turnip rape affect honey bees in Finnish oilseed cultivation. The interim report brings together the main results of the first growing season. The experimental protocol included four trial fields where spring turnip rape was cultivated. Each trial field was treated in a different way with neonicotinoid insecticides: without neonicotinoids, foliar spraying with neonicotinoids (thiacloprid) against pollen beetles and/or seed treatment with neonicotinoids (thiametoxam) against flea beetles. The plant density and crop growth was determined in the trial fields. The number of honey bees and other pollinators was assessed with the applied line transect method during the growing season. Five test bee hives were located at the edge of each trial field. The condition of the bee hives was checked and the amount of bees and brood was counted 4-5 times during the summer season. Census was done also in autumn and in spring to get overwintering data. Bees and bee hive products from all test bee hives of the trial fields were analysed for residues of neonicotinoids. In addition, residues were analysed from samples collected as a survey from forty other bee hives in South-West Finland. Half of those bee hives were located close to oilseed cultivation and the other half far from oilseed cultivation. The crop growth was normal in three of the trial fields. In one trial field (seed treatment with neonicotinoids) the crop growth suffered probably because of too much varied drilling depth. According to the main results of the counting of pollinators, the number of honey bees in the trial fields was high when the crop growth was good and lower when crop growth was poor. In the field which was treated with foliar spraying with a neonicotinoid (thiacloprid) the number of honey bees decreased after the treatment. However, the number of honey bees clearly increased 2-3 days after the foliar treatment. The results of the first growing season did not show, that the use of neonicotinoids affects the success of bee colonies, which were located at the edge of the trial fields. Both the adult and the brood population dynamic curves showed typical levels and shape of bee and brood population development. The average range of food consumption of the bees during overwintering and the overwintering index (the relation of the number of adult bees in spring compared to the number of adult bees in the beginning of overwintering) showed also typical levels compared to normal bee colonies in South-West Finland. Two bee hives lost their queen during fall and winter. One of those hives was located in the field without use of neonicorinoids and the other in the field in which a seed treatment neonicotinoid was used. The winter losses of the test bee colonies did not differ from the average winter losses (7 %) in the South-West of Finland. The results of the residue studies showed that residues of neonicotinoids migrate with pollen and nectar into bee hives. The total residue levels of seed treatment neonicotinoids, thiametoxam and chlothianide, were at such a low level, that acute harm to bees is unlikely. However, the residue levels, especially in nectar, resulted in an estimated exposure which is close to the chronic and acute sublethal risk limits presented in literature. Therefore, that kind of risk cannot fully be excluded. The neonicotinoid (thiacloprid) used as a foliar spray resulted in higher residue levels in certain samples than the seed treatment neonicotinoids, and on the other hand in higher estimated exposures. However, the toxicity of the neonicotinoids used in foliar sprayings is only a hundredth of the toxicity of the ones used in seed treatment and therefore the exposure is estimated to be clearly below the risk limits. The Neomehi project continued with the new field experiments in this summer. Final report based onwider research data will be published in 2015.

Neomehi-hankkeessa tutkitaan minkälaisia vaikutuksia rypsinviljelyssä käytettävillä, neonikotinoideja sisältävillä, torjunta-aineilla on mehiläisiin suomalaisessa öljykasvin viljelyssä. Väliraportti kokoaa yhteen kaksivuotisen Neomehi-hankkeen keskeisimmät tulokset ensimmäiseltä kasvukaudelta. Koejärjestely sisälsi neljä kenttäkoetta, joissa viljeltiin rypsiä. Neonikotinoideja sisältäviä insektisidejä käytettiin eri tavoin kullakin pellolla. Koepellolla joko ei käytetty neonikotinoideja tai ruiskutettiin neonikotinoidillakirppoja vastaan ja/tai käytettiin neonikotinoidilla peitattua siementä rapsikuoriaisia vastaan.Kasvien kasvua ja kasvutiheyttä seurattiin ja pelloilla vierailevien mehiläisten ja muiden pölyttäjien lukumäärä määritettiin kasvukauden aikana. Kunkin pellon laidalla pidettiin viittä mehiläispesää. Mehiläispesien kuntoa seurattiin ja mehiläisten ja niiden jälkeläisten lukumäärä laskettiin vähintään neljällä eri tarkastuskäynnillä kesän aikana. Vahvuuslaskentoja tehtiin myös syksyllä sekä seuraavana keväänä jotta saatiin tarkempaa tietoa talvehtimisesta. Mehiläisiin ja mehiläispesän tuotteisiin kerääntyviä neonikotinoidien jäämiä analysoitiin kaikista kenttäkokeen pesistä. Lisäksi jäämiä tutkittiin neljästäkymmenestä näytteestä, jotka kerättiin otantana Lounais-Suomessa sijaitsevilta mehiläistarhoilta. Otantatutkimukseen pesät valittiin siten, että puolet pesistä sijaitsi lähellä rypsinviljelyä ja puolet kaukana. Kasvien kasvu ja kukintojen tiheys oli normaalia kolmella koepellolla. Yhdellä pellolla kasvu ei ollut niin hyvää johtuen todennäköisesti väärästä kylvösyvyydestä. Pölyttäjälaskennat osoittivat, että pääsääntöisesti mehiläisten lukumäärä pellolla oli korkea kun kasvin kasvu oli hyvä ja kukintoja runsaasti ja toisaalta taas pölyttäjien lukumäärä alhainen kun kasvin kasvu heikkoa. Koekentällä, joka käsiteltiin neonikotinoidi ruiskutuksella, ei mehiläisiä juuri havaittu heti ruiskutuksen jälkeen. Muutama päivä käsittelystä mehiläisten lukumäärä pellolla oli kuitenkin palautunut ruiskutusta edeltäneeseen tilaan. Ensimmäisen kauden tulosten perusteella ei voitu havaita, että neonikotinoideilla olisi ollut vaikutuksia koekenttien läheisyydessä olevien mehiläisyhdyskuntien kuntoon. Mehiläisten sekä niiden jälkeläisten lukumäärän kehittyminen kasvukauden aikana oli normaalia kaikilla koekentillä. Myös talvenaikainen ruoankulutus sekä talvehtimisindeksi (mehiläisten ja niiden jälkeläisten lukumäärän suhde syksyllä ja keväällä) asettuvat tyypillisiin arvoihin, joita mehiläisyhdyskunnille on mitattu Lounais-Suomessa. Talven aikana kaksi pesää menetti kuningattaren. Toinen pesä oli koekentällä, jota ei käsitelty neonikotinoideilla ja toinen kentällä, jossa neonikotinoideja oli käytetty siementen peittaukseen. Talvehtimistappiot eivät eroa koko Suomen keskiarvosta (7%). Jäämätutkimusten perusteella neonikotinoidien jäämiä siirtyy siitepölyn ja meden mukana mehiläispesään. Peittausaineiden (tiametoksaamin, klotianidiinin) yhteenlasketut jäämätasot ovat niin alhaisia, että akuutti haitta mehiläisille on epätodennäköistä. Kuitenkin, mitatut jäämäpitoisuudet etenkin medessä johtavat arvioon altistumistasosta, joka on lähellä kirjallisuudessa esitettyjä kroonisia ja akuutteja subletaaleja riskirajoja. Jäämätulosten perusteella ei voida siis täysin pois sulkea tämäntyyppistä riskiä. Ruiskutteena käytetyn neonikotinoidin (tiaklopridi) jäämäpitoisuudet ovat näytteissä huomattavasti korkeampia kuin peittausaineiden pitoisuudet ja näin ollen myös mehiläinen altistuu suuremmille pitoisuuksille. Kuitenkin, johtuen ruiskutteiden sisältämien neonikotinoidien huomattavasti alemmasta myrkyllisyydestä, tässä tutkimuksessa arvioitu altistuminen jää selkeästi alle riskirajojen.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; rypsi; torjunta-aineet; mehiläiset; ympäristövaikutukset